Which antibiotic therapy, if any, is effective in reducing symptom severity and duration of acute bacterial sinusitis?. Issue 10 (October 2015) - Ellingsworth, Chase; Swofford, Sarah
Abstract : Evidence‐Based Answer : The use of antibiotics for acute bacterial sinusitis appears to reduce clinical failure rate at 7 to 15 days, although the clinical benefit over placebo is small (NNT=21). No antimicrobial therapy is superior to another and antibiotics are associated with more adverse effects (SOR: A, meta‐analyses). Antibiotic use does not significantly reduce symptom severity (SOR: B, RCT).